Hodographic study of plane micropolar fluid flows - Indrasena Adluri (International Journal of Mathematics and Mathematical Sciences)
Equations of steady flow of a plane micropolar fluid are transformed to the hodograph plane by means of the Legendre transform function of the streamfunction. Results are summarized in the form of a theorem, some flow problems are investigated as applications of this theorem and exact solutions and geometry of the flow are obtained in each case.